Pembelajaran Menulis Cerpen dengan Menggunakan Metode Sugesti-Imaji pada Siswa Kelas XI SMK PGRI Subang - Maulana, Irpan (Jurnal Artikula, 2020)
Basically everyone is capable of writing, it's just that writing skills need to be trained on an ongoing basis. Apart from needing to be trained on an ongoing basis, the selection of learning methods also needs to be considered, considering that students' ability to write can be categorized as still weak. The learning method used in this research is the suggestion-imagination method. The formulation of the problems in this study are: (1) How is the ability of class XI students of SMK PGRI Subang in writing short stories? (2) How is the ability of class XI students of SMK PGRI Subang in writing short stories using the suggestion-imagination method? (3) How to improve the ability of class XI students of SMK PGRI Subang in learning to write short stories using the suggestion-imagination method? The main objective in this study is how to improve student learning outcomes after using the suggestion-imagination method. The research method used was pre-experimental with a research design in the form of experimental one group pretest-posttest design. The research was conducted at SMK PGRI Subang with the research subjects of class XI TKJ 1 as the experimental class. Sampling in this study using purposive sampling technique or sample aims. Based on statistical data with the help of the SPSS 23 program, the initial test average value was 56.54 and the final test obtained an average value of 75.28. Based on these calculations, it can be seen that there is an increase in the average value of the posttest compared to the pretest before using the suggestion-imaginary method. Thus the use of the suggestion-imagination method in learning to write short stories is able to provide significant changes and this is proven to be effectively applied in learning to write short stories.